ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN ASUPAN MAKANAN PASIEN THALASEMIA DI RSUD BANYUMAS - Betty Irmawati; Agus Prastowo; J Supadi; Yuniarti Yuniarti (JURNAL RISET GIZI, 2017)
THE ANALYSIS OF FACTORS RELATED TO FOOD INTAKE ON THALASSEMIA PATIENT IN BANYUMAS HOSPITALBackground : Nutritional deficiencies in long time can impair growth in thalassemia children, and the low energy reserves and existence of hypercatabolic make nutrition status of children leading to wasting condition. Result of initial survey in Instalation of Integrated Thalassemia Service, Banyumas Hospital, energy intake on thalassemia patient 54% is deficiency category. Objective : To find factors related to food intake on thalassemia patient who receive regular blood transfusion in Banyumas Hospital.Methods : The kind of research is inferential with cross sectional design. The number of subject is 57 patients, age 6-15 years. Statistic analysis is used to chi square test.Results : The part of subject energy intake is deficit, with mean of energy intake is 85,74 ± 13,62% AKG. All of subject do not experience side effect of gastrointestinal disturbance from consuming iron chelation. 66,7% subject consume supplement according to doctor prescription, 57,9% subject have good of nutrition knowledge, and 63,2% subject get good support from family. Result of statistic analysis is p value for consuming supplement variabel is 0,003; 0,57 for nutrition knowledge and 0,01 for family support.Conclusion : There are relation about consuming supplement and family support with food intake, but there are no relation about nutrition knowledge with food intake.